Crosstalk Between Autophagy and Cerebral Ischemia - Sun, Yulin; Zhu, Yuanhan; Zhong, Xiaojun; Chen, Xinle; Wang, Jun; Ying, Guozheng (Frontiers in Neuroscience, 2019)
With the use of advanced electron microscopy and molecular biology tools, several studies have shown that autophagy is involved in the development of ischemic stroke. A series of molecular mechanisms are involved in the regulation of autophagy. In this work, the possible molecular mechanisms involved in autophagy during ischemic stroke were reviewed and new potential targets for the study and treatment of ischemic stroke were provided.